XAS study on electron transfer in cobalt complexes containing catecholate and semiquinone ligands - Park, JC; Kim, DK; Jung, OS; Choy, JH (EDITIONS PHYSIQUE, 1997)
XAFS measurements have been carried out at both room temperature and 100 K on complexes of general form of Co-III(N-N)(DBQ), where N-N is 1,10-phenanthroline(phen), N,N,N',N'-tetramethylethlenediammine(tmeda), and DBQ is the 3,6-di-tert-butylcatechol or 3,6-di-tert-semiquinone ligands. Co K-edge XAFS spectra disclosed that Co(tmeda)(DBQ)(2) is locked in a charge distribution of Co-III(tmeda)(3,6-DBSQ)(3,6-DBCat), while Co(phen)(DBQ)(2) is accompanied by the transition of Co-III/Co-II dependent on temperature.
Keywords: ABSORPTION FINE-STRUCTURE